2020
DOI: 10.1007/s00347-020-01100-x
|View full text |Cite
|
Sign up to set email alerts
|

Analyse des Stellenwertes von „eLearning“ in der Augenheilkunde und Evaluierung einer „eLearning-App“

Abstract: Zusammenfassung Hintergrund Ziel der Studie war die Analyse des Stellenwertes von „eLearning“ im Lern- und Fortbildungsverhalten von Augenärzten in Deutschland sowie die Bewertung der Akzeptanz einer neuen „eLearning“-Anwendersoftware (App). Material und Methoden Ophthalmologische Weiterbildungsassistenten und Fachärzte wurden im Rahmen von Fortbildungsveranstaltungen mittels eines Fragebogens nach ihren Fortbildungsaktivitäten befragt. Des Weiteren erfolgte nach Vorstellung und Anwendung einer „eLearning-App… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
3

Year Published

2021
2021
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 12 publications
0
3
0
3
Order By: Relevance
“…Web-based learning is an accessible and effective learning method that educators and students use to supplement or replace traditional learning, especially during the outbreak of the COVID-19. In recent years, a large number of studies have reported that e-learning has been widely used in various disciplines, such as clinical medical education ( Aloia and Vaporciyan, 2019 ; Grabowski et al, 2020 ; Tretter et al, 2020 ), nursing education ( Sinclair et al, 2016 ; Voutilainen et al, 2017 ; Kim and Park, 2019 ), and higher education ( Chu et al, 2019 ; He and Yusop, 2020 ; Zhang et al, 2020 ). Therefore, the advantages of e-learning, such as flexibility in learning, convenience in enabling learners to review subjects, and more vivid and authentic displays of cases, are also recognized by educators and learners ( Fagö-Olsen et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Web-based learning is an accessible and effective learning method that educators and students use to supplement or replace traditional learning, especially during the outbreak of the COVID-19. In recent years, a large number of studies have reported that e-learning has been widely used in various disciplines, such as clinical medical education ( Aloia and Vaporciyan, 2019 ; Grabowski et al, 2020 ; Tretter et al, 2020 ), nursing education ( Sinclair et al, 2016 ; Voutilainen et al, 2017 ; Kim and Park, 2019 ), and higher education ( Chu et al, 2019 ; He and Yusop, 2020 ; Zhang et al, 2020 ). Therefore, the advantages of e-learning, such as flexibility in learning, convenience in enabling learners to review subjects, and more vivid and authentic displays of cases, are also recognized by educators and learners ( Fagö-Olsen et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Webbasierte Trainingstools stellen zudem in der Augenheilkunde zum jetzigen Zeitpunkt kaum Alternativen dar. Diese sind zum einen momentan in zu geringem Ausmaß auf dem Markt [ 2 ] und zum anderen häufig an Ärzte in der Facharztausbildung gerichtet. Trainingstools, die Untersuchungstechniken simulieren, sind zwar bereits etabliert [ 6 ], werden aber derzeit nicht am heimischen PC angewandt.…”
Section: Diskussionunclassified
“…Dies ist durch mehrere Faktoren bedingt. Wie frühere Studien bereits zeigten, beruht die Akzeptanz für neue Lehrformate auf mehreren Faktoren [7]. Neben der Benutzerfreundlichkeit und dem unkomplizierten Abrufen von Onlineinhalten, verfügt das neue Lehrkonzept über weitere wesentliche Vorteile gegenüber dem traditionellen Lehrsystem.…”
Section: Diskussionunclassified